ASP.net web developer's guide - Turtschi, Adrian (Rockland, Mass. : Syngress, 2002)
All the essential information needed to take full advantage of Microsoft's newest Web development platform What is ASP .NET ASP.NET is a revolutionary new programming framework that enables the rapid development of powerful web applications and services. Part of the emerging Microsoft .NET Platform, it provides the easiest and most scalable way to build, deploy and run distributed web applications that can target any browser or device. ASP.NET (formerly referred to as ASP+) is more than the next version of Active Server Pages (ASP); it is a unified Web development platform that provides the services necessary for developers to build enterprise-class Web applications. ASP .net Web Developer's Guide will teach Web developers to quickly and easily build solutions for the Microsoft .NET platform. Programmers who are expert in asp and other languages will find this book invaluable. This book will appeal to all web developers - regardless of what language they are using or what platform they will be using You can take it with you. The book comes packaged with Syngress' revolutionary wallet-sized CD containing a printable HTML version of the book, all of the source code examples and demos of popular ASP .NET programming tools Comprehensive Coverage of the Entire .net Framework for B2B commerce.
Includes index.
Keywords: Active server pages; Microsoft .NET Framework; Programming languages (Electronic computers).; Electronic books